\[\boxed{\text{489\ (489).}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[n^{3} + 3n^{2} + 2n =\]
\[= n \cdot \left( n^{2} + 3n + 2 \right) =\]
\[= n \cdot \left( n^{2} + 2n + n + 2 \right) =\]
\[= n \cdot ((n \cdot (n + 1) + 2 \cdot (n + 1) =\]
\[= n \cdot (n + 1) \cdot (n + 2) -\]
\[последовательные\ \]
\[натуральные\ числа,\ \]
\[следовательно,\ одно\ кратно\ 2,\ \]
\[другое\ кратно\ 3,\ тогда\ \]
\[произведение\ кратно\ 6.\ \]
\[Что\ и\ требовалось\ доказать.\]
\[\boxed{\text{489.}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[a = 3x + 1;\ \ \ \ \ b = 9y + 7.\]
\[4a + 2b =\]
\[= 4 \cdot (3x + 1) + 2 \cdot (9y + 7) =\]
\[= 12x + 4 + 18y + 14 =\]
\[= 12x + 18y + 18 =\]
\[= 3 \cdot (4x + 6y + 6) \Longrightarrow делится\ \]
\[на\ 3,\ тогда\ и\ сумма\ делится\ на\ \]
\[3.\ \]
\[Что\ и\ требовалось\ доказать.\]